Theories of Community Collaboration to Advance Age-Friendly Community Change. (16th September 2021) - Greenfield, Emily A; Black, Kathy; Oh, Patricia; Pestine-Stevens, Althea
Abstract: The age-friendly communities movement has grown rapidly in global prominence over the past 2 decades. However, theories to guide multisectoral action toward age-friendly community change have been slower to develop. We demonstrate the value of drawing on theories of community collaboration to inform age-friendly community efforts across engagement, planning, implementation, and measurement. We introduce 3 theories—Asset-Based Community Development, Strategic Doing, and Collective Impact—each with principles and strategies for guiding multisectoral group processes toward long-term and systematic community change. While distinct from each other, these theories collectively suggest the importance of incorporating a more explicit community-building approach within the age-friendly communities movement. We describe the implications of this integrative theory development for bolstering sustainable and comprehensive practices and policies to improve environments for aging across diverse communities.